Collusion and Durability - Roland Strausz; Dan Sasaki (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
We develop a model to show that cartels that produce goods with lower durability are easier to sustain implicitly. This observation gen- erates the following results: 1) implicit cartels have an incentive to pro- duce goods with an inefficiently low level of durability; 2) a monopoly or explicit cartel is welfare superior to an implicit cartel; 3) welfare is non-monotonic in the number of firms; 4) a regulator may demand inefficiently high levels of durability to prevent collusion.
urn:nbn:de:bvb:19-epub-13306-9
Keywords: L15; 330; cartels; collusion; durability